Routing model of sediment yield for a representative Himalayan drainage Basin, India - Ravindra K. Pande (Faculty of Geography, Universitas Gadjah Mada, 1991)
For a large watersheds sediment yield can be more accurately estimated if the large watersheds is divided into sub-watersheds to compensate for non-uniformly distributed sediment sources. The effect of drainage basin hydraulics can be included by routing the sediment yield from sub-watersheds to the large watersheds outlet Sediment routing increase prediction accuracy and determines individual watersheds contribution to the total sediment yield.